Physiolysis for Metatarsal Bracketed Epiphysis : Surgical/Technical Tips - Minkowitz, Barbara; Spingarn, Colleen M.; Bertsch, Aidan; Fekete, Julia M.; Rienzo, Jason A.; Davis, Ellen; Shah, Neil; Mubarak, Scott (Journal of the Pediatric Orthopaedic Society of North America, 2023)
<span class="NormalTextRun SCXW1156312 BCX0" data-ccp-charstyle="normaltextrun" data-ccp-charstyle-defn=""ObjectId":"932c13ce-6912-4a32-bc46-c964d35911ae|122","ClassId":1073872969,"Properties":[469775450,"normaltextrun",201340122,"1",134233614,"true",469778129,"normaltextrun",335572020,"1",469778324,"Default Paragraph Font"]">Metatarsal bracketed epiphysis is an uncommon disorder that results in the diaphyseal ossification of the tubular bones due to abnormally located/continuous physeal tissue along the diaphysis. This interferes with normal growth by causing progressive shortening and an angular deformity of the affected medially convex bone. This disorder progresses in four stages: (1) lack of ossification along the longitudinal epiphyseal bracket, (2) formation of ossification centers both proximally and distally, (3) unification of ossification centers along the longitudinal diaphysis, (4) complete closure of the bracket. Treatment of this condition is primarily surgical and varies depending on the stage. Our recommendation is treatment with early physiolysis to remove the excess growth plate, a surgical technique which has been documented in the literature by Choo & Mubarak. Due to the rarity of the condition, there are limited case reports documented in the literature. To our knowledge, there are no visual demonstrations of surgical technique. Treatment with early physiolysis gives the greatest potential for correction of longitudinal and angular deformity of the bone as the patient grows it allows for natural growth to counteract the present angulation. This case report reviews the surgical treatment of a skeletally immature, 8-year-old female with stage 3 bracketed epiphysis with central physiolysis, using PMMA to block the regrowth of the bar.